2021
DOI: 10.1007/s10875-021-01141-0
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Defects in B Cell Development and Differentiation, T Cell Exhaustion and Altered Unconventional T Cell Generation Characterize Human Adenosine Deaminase Type 2 Deficiency

Abstract: Purpose Deficiency of adenosine deaminase type 2 (ADA2) (DADA2) is a rare inborn error of immunity caused by deleterious biallelic mutations in ADA2. Clinical manifestations are diverse, ranging from severe vasculopathy with lacunar strokes to immunodeficiency with viral infections, hypogammaglobulinemia and bone marrow failure. Limited data are available on the phenotype and function of leukocytes from DADA2 patients. The aim of this study was to perform in-depth immunophenotyping and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 75 publications
3
43
0
1
Order By: Relevance
“…Features of macrophage activation syndrome/hemophagocytic lymphohistiocytosis (MAS/HLH), haemolytic anemia (non-immune), and persistent cytopenias (with a hypercellular bone marrow) were noted in this patient ( 53 ). MAS/HLH was also been reported in the first descriptions of this disease, besides many published and unpublished observations ( 1 , 26 , 38 ).…”
Section: Spectrum Of Clinical Manifestationsmentioning
confidence: 65%
See 3 more Smart Citations
“…Features of macrophage activation syndrome/hemophagocytic lymphohistiocytosis (MAS/HLH), haemolytic anemia (non-immune), and persistent cytopenias (with a hypercellular bone marrow) were noted in this patient ( 53 ). MAS/HLH was also been reported in the first descriptions of this disease, besides many published and unpublished observations ( 1 , 26 , 38 ).…”
Section: Spectrum Of Clinical Manifestationsmentioning
confidence: 65%
“…The authors also reported arrest in B cell development in the bone marrow at the pro-B to pre-B cell stage and defect in terminal B cell differentiation. Authors have also shown that healthy heterozygous carrier state for DADA2 showed intermediate values of lymphocyte phenotypes and functions in comparison to DADA2 patients and healthy controls, further highlighting the role of heterozygous state ( 26 ). Thus, immune defect in patients with DADA2 deficiency may present with myriad immunological aberrations ( 26 ).…”
Section: Spectrum Of Clinical Manifestationsmentioning
confidence: 93%
See 2 more Smart Citations
“…Besides mild immunodeficiency, the associated impairment of the immune system may cause various autoinflammatory symptoms. Additionally, the hematopoietic system may be affected, resulting in mild to severe cytopenia of all lineages (anemia, lymphopenia and thrombocytopenia) ( 1 4 , 8 15 ).…”
Section: Introductionmentioning
confidence: 99%